Association between oxygen debt (DEOx) variability over time and clinical outcomes in critically ill COVID-19 patients: an observational study - Eduardo Tuta-Quintero; Alirio Bastidas-Goyes; Henry Robayo-Amortegui; Michel Pérez-Garzón; Isacio Serna-Palacios; Cristian Peña-Quimbayo; Julian Espitia; Daniel Pinto; Johan Rincón; Juan Sánchez; Jesus Pérez (BMC Pulmonary Medicine)
Abstract Background Oxygen debt (DEOx) quantifies oxygen deficit during shock, reflecting the transition to anaerobic metabolism due to decreased oxygen delivery (DO₂). This study aimed to analyze the temporal variation of DEOx values and their association with invasive mechanical ventilation (IMV) requirement and survival in patients with severe COVID-19. Methods We conducted a retrospective cohort study including adult patients admitted to the ICU with confirmed SARS-CoV-2 infection at Clínica Universidad de La Sabana (Colombia) between July 2020 and December 2021. DEOx was calculated using two validated formulas: one based on lactate (DEOx1) and another incorporating lactate and base excess (DEOx2). Variability in DEOx was assessed at different time points (≤6h, 6-12h, 12-24h, >24h) and its association with IMV and survival outcomes was analyzed. Results A total of 597 patients were included, of whom 150 (25.1%) died. DEOx1 within 6 hours was -6.87 (SD: 23.72) in patients requiring IMV by day 7, compared to -1.2 (SD: 7.83) in patients without IMV (p=0.004). DEOx2 within 6 hours on day 7 was -7.92 (SD: 30.7) vs. -1.57 (SD: 14.65) (p=0.027), and between 6 and 12 hours, it was 1.24 (SD: 14.92) vs. -3.54 (SD: 9.34) (p<0.001). 24 hours (SD: 36.09) in deceased patients on day 7, compared to -2.09 (SD: 14.26) in survivors (p<0.001). Between 6 and 12 hours, DEOx1 was 0.51 (SD: 11.49) vs.-2.27 (SD: 12.32) (p=0.016). At more than 24 hours, it was 3.21 (SD: 9.22) vs. -3.8 (SD: 20.91) (p<0.001). Similar trends were observed on days 14 and 28. DEOx2 within 6 hours on day 7 was -19.02 (SD: 35.3) vs. -1.36 (SD: 14.31) (p<0.001), and between 6 and 12 hours, it was 7.57 (SD: 18.78) vs. -1.94 (SD: 11.73) (p<0.001). At more than 24 hours, it was 2.6 (SD: 10.75) vs. -4.54 (SD: 17.26) (p<0.001). This pattern persisted on days 14 and 28. Conclusion DEOx variability in critically ill COVID-19 patients was significantly associated with IMV need and mortality. Higher DEOx values at ≤6h and persistent metabolic derangement beyond 24h correlated with worse outcomes.